2013
DOI: 10.1128/cvi.00672-12
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequencing Reveals Mutations Potentially Related to the Overattenuation of a Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus

Abstract: bHighly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) continues to evolve when serially passaged in Marc-145 cells. In this study, we analyzed the genomic and antigenic variants of HP-PRRSV strain JXA1 during in vitro passage. Protective efficacies of JXA1 from passages 100, 110, 120, 140, and 170 against the high-virulence parental virus were evaluated by inoculating pigs with each of these viruses and then challenging with JXA1 from passage 5 at 28 days postimmunization. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
0
17
0
3
Order By: Relevance
“…The isolates identified in this study (15GD2, 15GD3, 15HUN1, and 15HUN2) were potential recombinants associated with 2009–2010 HP-PRRSV-like strains and were located in sublineage 10.6. Sublineage 10.7 consisted of JXA1 derivatives by serial passaging in MARC-145 cells [38, 39] and potential vaccine JXA1-R (JXA1 P80)-like strains. In sublineage 10.7, 10 isolates (15ZJ2, 15ZJ3, 15HUN3, 15LN2, 15JX2, 15JX3, 15JX4, 15HEN3, 15SC1, and 15SC2) from the present study were identified as potential vaccine JXA1-R-like strains with a 30-aa deletion in Nsp2.…”
Section: Resultsmentioning
confidence: 99%
“…The isolates identified in this study (15GD2, 15GD3, 15HUN1, and 15HUN2) were potential recombinants associated with 2009–2010 HP-PRRSV-like strains and were located in sublineage 10.6. Sublineage 10.7 consisted of JXA1 derivatives by serial passaging in MARC-145 cells [38, 39] and potential vaccine JXA1-R (JXA1 P80)-like strains. In sublineage 10.7, 10 isolates (15ZJ2, 15ZJ3, 15HUN3, 15LN2, 15JX2, 15JX3, 15JX4, 15HEN3, 15SC1, and 15SC2) from the present study were identified as potential vaccine JXA1-R-like strains with a 30-aa deletion in Nsp2.…”
Section: Resultsmentioning
confidence: 99%
“…Codon 58 (encoded by ORF5) is located in the second hypervariable region, which is known to be under selective evolutionary pressure (Delisle et al., ), as well as to significantly influence the susceptibility of the mutant viruses to a neutralizing antibody (Kim et al., ). It was noted that among ten codons predicted to differ in the strength of selective pressure between the typical clade and the highly pathogenic clade, only codon 43 (encoded by ORF4) was demonstrated to occur during the in vitro attenuation process of different strains of highly pathogenic type 2 PRRSV (An et al., ; Leng et al., ), and codon 172 of that gene was suggested to contribute to the in vitro over‐attenuation of a highly pathogenic type 2 PRRSV (Yu et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…These results were likely due to the essential functions of these sites, which are subject to similar and strong selection constraints. Other differentially selected codons (codons 43 and 172 of ORF4/GP4, P < 0.01) were revealed to be related to the in vitro attenuation/over‐attenuation processes of highly pathogenic type 2 PRRSV (An et al., ; Leng et al., ; Yu et al., ). Those sites, however, did not change during the processes of attenuation and reversion to virulence of typical type 2 PRRSV as reported elsewhere (Allende et al., ; Grebennikova et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Live attenuated vaccine immunization can stimulate humoral immunity and cellular immunity in pigs, bring broader protection against heterologous PRRSV strains. At present, three additional commercial Highly pathogenic PRRS modified live virus vaccines (HP PRRS MLV), JXA-1R [1][2][3], TJM-F92 and HuN4-F112, were all introduced into the Chinese swine industry, all providing adequate protection of pigs to HP-PRRSV infection [4,5].…”
Section: Introductionmentioning
confidence: 99%